Application of complex training within strength and conditioning programmes - Comyns, T. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Alternating a resistance exercise with a plyometric exercise is referred to as "complex training". Post-activation potentiation is the physiological rationale for complex training. This form of training is widely used to improve strength, power and stretch-shortening cycle (SSC) function. Enough is not known, however, on how this form of training can be optimised. Many factors such as the rest interval and the magnitude of the resistance exercise can have an influence on the efficiency of this training modality. More research is needed so that strength and conditioning coaches can best apply the principles of complex training to athletes` strength and power programmes.